The humanities and humanism of the future - Marín Murillo, Asdrúbal (2026)
This is an essay on humanism, in which the contribution of humanities to costarrican society is analyzed, especially the role that the School of General Studies of the University of Costa Rica has played in this context. A general synthesis of the humanist tradition is presented, and also, the historical links between western humanism and the development of science, technology and other forms of knowledge. The author emphasizes the fact that, despite the scientific progress, human societies are not finding their cultural goal. So, the role of humanities is questioned, and asks for a new way of humanism for a new era.